A COMPREHENSIVE ANALYSIS OF MYSTICAL THOUGHT OF RUMI: A PROFOUND EXPLORATION OF MAGNUM OPUS MATHNAVI MAANAVI - Dr. Muhammad Zaffar Iqbal Saeedi; Dr Faizan Ahmed; Unsa Khan; Dr. Ambreen Ali; Dr. M. Shafiq Anjum; Ghazanfar Ali Hussain; Muhammad Akbar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2023)
Rumi’s Mathnavi Maanavi is considered as one of the most significant works of mystical literature in Persian language. In this magnum opus, Rumi delves deep into the nature of divine love, the relationship between the human and the divine, and the journey of the soul towards union with Almighty Allah. One of the key themes in the Mathnavi Maanavi is the concept of "annihilation" or "fana". Rumi uses this term to describe the process by which the individual ego is dissolved and merged into the divine. This process is achieved through meditation, contemplation, and self-reflection, and it is central to Rumi’s understanding of the mystical path. Rumi also emphasizes the importance of love as a means of attaining union with the divine. He describes love as a transformative force that can lead individuals towards the highest levels of spiritual attainment. This love is not limited to romantic or human relationships, but extends to all of creation and ultimately to Almighty Allah. Another important theme in the Mathnavi Maanavi is the idea of the "Divine Breath". Rumi uses this term to describe the creative and life-giving power of Almighty Allah. He sees the Divine Breath as a unifying force that connects all of creation, and he emphasizes the importance of recognizing and submitting to this force in order to achieve spiritual growth. Throughout the Mathnavi Maanavi, Rumi also reflects on the nature of human suffering and the role it plays in the spiritual journey. He argues that suffering can be a catalyst for growth and transformation, and that it can lead individuals towards a deeper understanding of themselves and the divine. Overall, Rumi’s mystical thought in the Mathnavi Maanavi emphasizes the importance of spiritual transformation, love, and submission to the divine. He sees the human journey towards union with Almighty Allah as a process of self-discovery and self-transcendence, and he offers insights and guidance to individuals seeking to embark on this path.